The impacts of performance-based assessment on reading comprehension achievement, academic motivation, foreign language anxiety, and students’ self-efficacy - Tahereh Heydarnejad; Fariba Tagavipour; Indrajit Patra; Ayman Farid Khafaga (Language Testing in Asia, 2022)
Abstract The types of assessment tasks affect the learners’ psychological well-being and the process of learning. For years, educationalists were in search of finding and implementing accurate and convenient approaches to assess learners efficiently. Despite the significant role of performance-based assessment (PBA) in affecting second/foreign language (L2) learning processes, few empirical studies have tried to explore how PBA affects reading comprehension achievement (RCA), academic motivation (AM), foreign language anxiety (FLA), and students’ self-efficacy (SS-E). To fill this lacuna of research, the current study intended to gauge the impact of PBA on the improvement of RCA, AM, FLA, and SS-E in English as a foreign language (EFL) context. In so doing, a sample of 88 intermediate EFL learners were randomly divided into experimental group (EG) and CG (control group). During this research (16 sessions), the learners in the CG (N = 43) received the tradition assessment. In contrast, the learners in the EG (N = 45) were exposed to some modification based on the underpinning theories of PBA. Data inspection applying the one-way multivariate analysis of variance (i.e., the one-way MANOVA) indicated that the learners in the EG outperformed their counterparts in the CG. The results highlighted the significant contributions of PBA in fostering RCA, AM, FLA, and S-E beliefs. The implications of this study may redound to the benefits of language learners, teachers, curriculum designers, and policy makers in providing opportunities for further practice of PBA.